COUNTERFEITS AND THEIR COSTS - Hien, Pham Thi My; Trang, Nguyen Thi Mai (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
Counterfeiting is increasing and becoming a complicated issue across different countries in the world and Vietnam isÂ not exceptional, so the policy makers and managers always try to find ways to face with the counterfeiting and reduceÂ counterfeit products in the market. This paper attempts to investigate determinants that impact on consumersâ attitudeÂ toward non-deceptive counterfeit products and behavioral intention to purchase them. Using a data set collected fromÂ a sample of 176 consumers we found that social cost has an impact on consumersâ attitude and purchase intentiontoward counterfeit products. Moreover, the result indicates that intention to buy counterfeit products is influenced byÂ consumersâ attitude toward these products. These findings suggest that companies should rely on the social cost as theÂ main component of marketing communication messages to discourage consumption of fake products by implying theÂ seriously harmful consequences of these goods to society and economy.